Mineral nutrition of vegetable crops: XXXV. effects of calcium levels in nutrient solution upon the concentration of N, P, K, Ca, Mn and S in tomato plants (Lycopersicon esculentum Mill.) - Dechen, A.R.; Haag, H.P.; Sarruge, J.R.; Oliveira, G.D. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
Young tomato plants (Lycopersicum esculentum Mill.) cv. Santa Cruz, lineages Kada and Samano, were cultivated in solutions with different calcium concentrations (0 ppm, 50 ppm, 100 ppm, 200 ppm and 400 ppm Ca) with the following purposes: a) to study the effects of calcium on yhe growth of the plant; b) to correlate calcium supply and blossom-end rot; c) to correlate calcium supply and the nutrient concentrations in the tomato plant; d) to reveal nutritional differences between the lineages. Ninety days adter starting the different treatments, plants were collected and separeted into old leaves, new leaves, lower part of the stem, superior part of the stem and fruits. The plant material was dried and analysed for macro-nutrients. The main conclusions were: - the greates dried matter production was obtained with the supply of 388 ppm of calcium in the culture solution for the Kada lineage and of 400 ppm for Samano lineage; - for the lineage Samano a concentration of calcium in the solution (200 ppm) higher than for the lineage Kada (100 ppm) was necessary in order to prevent appearance of blossom-end rot; - the calcium concentration in fruits was not affected by the calcium concentration in the nutrient culture; - calcium added to the culture solution decreased the nitrogen concentration and increased the calcium concentratio in both lineage parts; - the concentration of the other nutrients presented differences in the lineage and in the analysed parts; - concentration of calcium in the culture solution brings an increased improvement in the magnesium concentration in leaves and in the superior part of the stem of the lineage Samano, while in parts of lineage Kada a decrease of magnesium concentration was observed.